Miqat Application in Determining the Qibla Direction of the Mosque - Ami, Miftahul Jannah; Ifrohati, Ifrohati (Universitas Islam Negeri Raden Fatah Palembang, 2022)
In this all-digital era, the use of Android devices is no longer just a medium for communication, but on your smartphone device, there are already many applications circulating on the Play store developed by software companies and astronomers that are easy to use to assist you in determining. qibla direction. To fulfill the need for information on the Qibla direction of a place, you have to activate the technology on your smartphone that provides real-world Qibla direction information, namely by using the miqat application. This research is to find out the method of using the miqat application in determining the Qibla direction and knowing how the Qibla direction of the Sultan Mahmud Badarudin Jayo Wikramo mosque and Al-Islam Muhammad Cheng Ho Mosque is using the Miqat application. This research is classified as field research, namely research conducted by direct observation of the object studied in the field, aiming to determine the level of accuracy of the use of the miqat application in determining the Qibla direction. The use of the Miqat application in determining the Qibla direction is a method that is very easy to use wherever you are, but before using the application, it is better if you first calibrate the magnetic compass on your smartphone by shaking the phone so that the needle on the compass is stable. The accuracy of the Qibla direction of the Sultan Mahmud Badarudin Jayo Wikramo Mosque and the Al-Islam Muhammad Cheng Ho Mosque with the Miqat application, that in terms of whether or not this application is accurate, in principle, depends on usage. If used in places that contain metal it will make the magnetic sensor on the compass inaccurate which results in degree deviations on the compass being affected by the magnetic field and the metal around it which will result in a larger deviation of degrees on the compass, this application should be used outside the building because in principle, the compass on the cellular relies on magnetic sensors and GPS on the smartphone itself.